Cardiovascular Aging and Physical Activity: Insights From Metabolomics - Lim, Ryan Mao Heng; Koh, Angela S. (Frontiers in Cardiovascular Medicine, 2021)
The purpose of this review is to explore how metabolomics can help uncover mechanisms through which physical activity may influence the progression of cardiovascular ageing. Cardiovascular ageing is a process of functional and structural changes in older adults which can progress to cardiovascular disease. Metabolomics profiling is an investigative tool that can track the diverse changes which occur in human biochemistry with physical activity and ageing. This mini-review will summarize published investigations in metabolomics and physical activity, with a specific focus on the metabolic pathways that connect physical activity with cardiovascular ageing.